THE DYNAMICS OF ISLAMIC CIVILIZATION IN THE PERSIAN REGION: A HISTORICAL STUDY - Arditya Prayogi; Lilik Riandita; Singgih Setiawan (Jurnal Keislaman, 2022)
The chapters in the history of Islamic civilization by historians are divided into classical, medieval, and modern periods. Islamic civilization itself is a civilization that spread widely to various regions, including the Persian region. Persia in its history deviates many relics that show how Islam is dynamic in each era. This article was written using a qualitative descriptive approach by describing the literature study method. From the results of the discussion, it is known that Islamic civilization in Persia is dynamic, and most of the relics left by the Shafavid dynasty. In addition, in the later period, Persian identification with Shia (teachings) became attached to each other as a result of the dynamics of Islam in this region.